Antibiotic susceptibility reporting and association with antibiotic prescribing: a cohort study. (April 2021) - Langford, Bradley J.; Daneman, Nick; Diong, Christina; Marchand-Austin, Alex; Adomako, Kwaku; Saedi, Arezou; Schwartz, Kevin L.; Johnstone, Jennie; MacFadden, Derek R.; Matukas, Larissa M.; Patel, Samir N.; Garber, Gary; et al.
Abstract: Objective: Selective reporting of antibiotic susceptibility test results may help guide appropriate antibiotic prescribing, particularly for urinary tract infections. Our objective was to describe laboratory urine culture susceptibility reporting practices and to estimate their impact on antibiotic prescribing in outpatients. Methods: We examined all positive urine cultures with Escherichia coli, Klebsiella pneumoniae, or Proteus mirabilis associated with an antibiotic prescription among outpatients over 65 years of age in Ontario, Canada from 2014 through 2017. We evaluated antibiotic prescribing in the empirical window (1–3 days before culture result) and in the directed window (0–5 days after culture result). Unadjusted and adjusted odds ratios were reported to estimate the association between reporting and prescribing. Results: In total 113 780 eligible urine cultures from 48 laboratories were included in the study cohort. Susceptibility reporting practices were highly variable between laboratories, with a range across antibiotics from norfloxacin ( n  = 5/48, 10.4% reporting) to nitrofurantoin ( n  = 40/48, 83.3% reporting). Reporting antibiotic susceptibility was associated with increased odds of prescribing that antibiotic in the directed window (aOR 2.98, 95%CI 2.07–4.28). At the laboratory level, the proportion of urine cultures reporting specific antibiotic susceptibility results was also associated with an increase in prescribing of that antibiotic in the empirical window (adjusted OR 1.23, 95%CI 1.13–1.33, per 25% increase in reporting). Conclusions: Laboratory reporting of antibiotic susceptibility results for urine cultures is associated with empirical and directed prescribing of the reported antibiotics. Laboratories can play an important role in guiding appropriate antibiotic selection for urinary indications.